An objective method of prognosticating the five-day mean 700-mb chart two to four days ahead - PANT, P. S.; DAS, S. K.; NATARAJAN, T. R. (MAUSAM, 1965)
A few grid points representing different portions of the area covered by the latitudes 35°N and 5"N and longitudes 65°E and 95°E were chosen, For each selected grid point prognostic equations based on linear regression were obtained for predicting the mean 700.mb cloud contour anomaly for a pentad from the corresponding contour anomaly for the first and middle days of the same pentad, Data for the 5-year period 1957-61 were utilised for obtaining the regression equations for July and data for the period 1958.62 for obtaining corresponding equations for January. The above prognostic equations were applied to a few situations in January 1963 and July 1962, in order to obtain the prognostic 5-day mean 700-mb charts two to four days ahead. The prognostic charts so obtained were compared with the actual charts and good agreement was noticed between them.